Zika Virus (ZIKV): A New Perspective on the Nanomechanical and Structural Properties - Maria Luiza de Araujo Dorneles; Ruana Cardoso-Lima; Pedro Filho Noronha Souza; Daniela Santoro Rosa; Tais Monteiro Magne; Ralph Santos-Oliveira; Luciana Magalhães Rebelo Alencar (Viruses, 2022)
Zika virus (ZIKV) is an arthropod-borne virus (arbovirus) from Flavivirus. In 2015, Brazil and other Latin American countries experienced an outbreak of ZIKV infections associated with severe neurological disorders such as Guillain–Barre syndrome (GBS), encephalopathy, and encephalitis. Here, a complete mechanical and structural analysis of the ZIKV has been performed using Atomic Force Microscopy (AFM). AFM analysis corroborated the virus mean size (~50 nm) and icosahedral geometry and revealed high mechanical resistance of both: the viral surface particle (~200 kPa) and its internal content (~800 kPa). The analysis demonstrated the detailed organization of the nucleocapsid structure (such as RNA strips). An interesting finding was the discovery that ZIKV has no surface self-assembling property. These results can contribute to the development of future treatment candidates and circumscribe the magnitude of viral transmission.